Analysis of the Current Status on Entrepreneurial Intentions among CrowdWorks Freelancers in Japan (International Journal of Applied Research in Management and Economics, 2024)
Entrepreneurship is vital for economic growth in Japan. However, the Global Entrepreneurship Monitor (GEM) report for 2022 reveals that Japan still lags behind in entrepreneurial intentions and attitudes. The purpose of this paper is to establish statistically the structural aspects of entrepreneurial intentions among Japanese social media freelancers by applying a social psychological approach, the Theory of Planned Behaviour. Furthermore, it aims to outline the framework and link it to future research activities. A total of 476 respondents were surveyed. While no significant differences in the variances of entrepreneurial intentions were found between platforms, three other factors showed significant distinctions when analysed for each variable. The mean score for perceived behavioural control stood at 2.213, aligning with the 2022 GEM report’s low rating. However, attitudes towards entrepreneurship (mean score 4.423) and entrepreneurial intentions (mean score 3.844) were moderate. Correlation analysis highlighted a strong positive and significant relationship between attitude and entrepreneurial intention, as well as positive and significant relationships between perceived behavioural control and entrepreneurial intention, and between subjective norm and entrepreneurial intention. Furthermore, path analysis using SPSS Amos indicated that perceived behavioural control may influence attitudes and subjective norms. Subsequent research should explore new variables in a broader sample, customised to participants’ cultural backgrounds.